(untitled) - McCormick, Blaine (San Francisco, CA, 2003)
The Lord is my shepherd, I shall not want. He maketh me to lie down in green pastures; He leadeth me bedside the still waters; He restoreth my soul. Today's professionals need reliable models to teach them how to become better leaders. In this remarkable book, leadership experts Blaine McCormick and David Davenport introduce us to a new kind of leader by offering a new image of leadership- the leader as shepherd. Drawing on the wisdom of the timeless Twenty-Third Psalm, King David's psalm, the authors provide professionals with ancient wisdom for grappling with today's leadership challenges. Shepherd Leadership offers a much-needed lens through which to consider our own leadership as well as the leadership of those around us. This important book teaches us important lessons about leadership: we can be vigilant without being adversarial, we can serve without being passive, and we can guide without commanding. Shepherd Leadership offers a visionary new model for transforming leadership practices in both corporate and small business settings. This is whole-person leadership. It's not just a matter of thinking or doing things a certain way. It's a fully integrated life- a matter of head and hand and heart. It's a way of thinking and doing and being.
Keywords: Bible. O.T. Psalms XXIII,Leadership; Criticism, interpretation, etc.,Religious aspects,Christianity